Is old really gold? : Status of elderly people under the international and regional human rights instruments - Karim, M.E. (2015)
The discussion on the human rights of elderly people is particularly crucial in present context. These golden people, who have tremendous contribution towards the gradual development of human civilization, are considered as ‘burden’ in many cases, treated as an ‘object of abuse and neglect’. While core international human rights instruments prohibit any sort of discrimination on the ground of, inter alia, ‘age’, the human rights of these group of people are routinely violated. The serious concern is that the rate of these people has been growing at an unprecedented pace and the United Nations has estimated that the number of these people will reach to 1 billion by the end of this decade, and 80% of these people will be from the low-and middle-class income countries. Different stakeholders have taken various stances to handle the situation. Even though some countries have enacted legislation to protect elderly people, there is no international binding legal instrument. This paper aims at exploring the rights of the older people under different provisions of the international and regional human rights instruments. These provisions will be assessed to explore their adequacy to protect the human rights of the elder people. Initiatives taken by major international bodies will be shared, and relevant municipal provisions of selected countries will be considered. Such a discussion is crucial for the policy makers towards adopting or adjusting their municipal legal framework for the elderly people.